Specific performance of IDT edge fingers - DANICKI, E.; GAFKA, T (Archives of Acoustics, 1990)
A rigorous field theory has been developed that allows to analyze the generation and detection performance of each metal strip in a system of a few of them. The theory shows that the edge strips of the system works differently as compared with these positioned inside the system. The familiar δ-function model however, can still be applied provided that the δ-sources of SAW are properly scaled and shifted from their position at the centres of the strips. The scaling factor and the shift magnitude (which are larger for the edge electrodes of IDT) are determined by theory. Some numerical and experimental examples are presented, which seem to agree well.